Post COVID-19 lockdown: measures and practices for dental institutes - Sausan Al Kawas; Natheer Al-Rawi; Wael Talaat; Zaid Hamdoon; Basheer Salman; Saad Al Bayatti; Waseem Jerjes; A. B. Rani Samsudin (BMC, 2020)
Abstract Resuming regular clinical activities at dental premises after the COVID-19 lockdown period or post COVID-19 is likely to be a challenge for all dental institutes. When returning to the dental practice or training, staff and students alike should abide by the new rules and regulations. In the process of controlling viral spread, clinical dental facilities face a higher risk of disease transmission among patients as well as clinical and non-clinical staff. Aerosols formation and diffusion into the surrounding air can be a real concern of viral transmission, if no protective measures are established. We aim in this review to present the currently implemented measures and propose changes in clinical dental facilities to minimize the risk of transmission. Dental professionals should be prepared to treat every patient as a suspected COVID-19 carrier and be ready to receive and manage an overwhelming number of patients. We suggest that dental practices establish a sensible workforce shift schedule, improve ventilation levels, reduce dental aerosol generating procedures, and develop a comprehensive guidance to Healthcare Workers to reduce the risk of COVID-19 transmission.